PENGGUNAAN METODE STORYTELLING UNTUK MENINGKATKAN KEMAMPUAN MENYIMAK CERITA KELAS V SD NEGERI OEBOBO 2 KOTA KUPANG - Tamonob, Essy Fance; Margareta, Karus M.; Kota, Martha K. (Journal of Character and ELementary Education, 2024)
This research aims to improve students' ability to listen to stories in learning using the storytelling method. This type of research is Classroom Action Research (PTK) with stages namely: Planning, Implementation, Observation, and Reflection. This research was located at SD Negeri Oebobo 2, Kupang City, with the research subjects being all 25 class V students at SD Negeri Oebobo 2, Kupang City. The data collection techniques used by researchers in conducting research include observation techniques, tests, and documentation techniques. The results of this research show that students' listening abilities through the use of the storytelling method have improved significantly. This can be proven by the average achievement of learning completeness for class V students, totaling 25 people, namely in cycle I the percentage of completeness was 72% (18 people completed), and in cycle II the percentage of completion was 100% (25 people completed). This increase in students' listening skills can be seen from the increase in the average score on the evaluation test. Another increase that occurred was in student activity in class which was assessed using the observation sheet provided by the researcher. Thus, from the results of the research above, researchers can conclude that using the storytelling method can improve students' listening skills